2022
DOI: 10.3389/fpubh.2022.1028235
|View full text |Cite
|
Sign up to set email alerts
|

Regional maldistribution of human resources of rehabilitation institutions in China Mainland based on spatial analysis

Abstract: ObjectiveWith the demand for rehabilitation has been increasing faster for the aging of China's population, the equity of rehabilitation resource has aroused great concern. This study aimed to analyze the spatial distribution and evolution of the human resources of rehabilitation institutions and propose targeted countermeasures and suggestions to promote optimal allocation.MethodsA total of 31 provinces in China Mainland were identified and geocoded. The spatial weight matrix was introduced to analyze the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…increased to a certain extent from 2010 to 2016 ( 62 ). Cheng et al found that the average density of health personnel increased from 1.60 in 2016 to 1.88 in 2019 ( 50 ). These studies implied a gradually expanding spatial aggregation of human resources for health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…increased to a certain extent from 2010 to 2016 ( 62 ). Cheng et al found that the average density of health personnel increased from 1.60 in 2016 to 1.88 in 2019 ( 50 ). These studies implied a gradually expanding spatial aggregation of human resources for health.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we use the queen collinearity matrix ( 49 ), and regions with common points or common edges are adjacent to each other. Since there is no neighboring province in Hainan Province, it is set that Hainan Province and Guangdong Province are mutually neighboring according to previous studies ( 50 , 51 ). The assignment rules are as follows:…”
Section: Methodsmentioning
confidence: 99%